2020
DOI: 10.1016/j.etap.2020.103399
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-induced Parkinsonism in mice is reduced using a novel contaminated water sediment exposure model

Abstract: The effects of heavy metals on human health have become an important area of study. For instance, acute manganese toxicity is known to induce Parkinsonism. Heavy metals including manganese enter the aquatic environment from both anthropogenic and natural processes. These metals accumulate within water sediments and their behavior is then dependent upon the sediment composition and phase. These metalsediment interactions remain to be explored within in-vivo animal studies. To study the effect of these interacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…had a shorter retention duration on the revolving rod than the control group (Chopra et al, 2021). Male Mn mice spent less time on the rota rod than control mice, according to Freeman et al (2020) the time spent on the rota rod by females after manganese exposure was not considerably reduced like that of the male. Daily intraperitoneal (i.p.)…”
Section: Effect Of Manganese Exposure In Neurobehavioural Alterationmentioning
confidence: 78%
See 3 more Smart Citations
“…had a shorter retention duration on the revolving rod than the control group (Chopra et al, 2021). Male Mn mice spent less time on the rota rod than control mice, according to Freeman et al (2020) the time spent on the rota rod by females after manganese exposure was not considerably reduced like that of the male. Daily intraperitoneal (i.p.)…”
Section: Effect Of Manganese Exposure In Neurobehavioural Alterationmentioning
confidence: 78%
“…However, when compared to controls, animals given 20 mg Mn/kg demonstrated a substantial reduction in the overall latency for falling off the rota rod (Cordova et al, 2013b) When comparing the Mn-treated group to the control group, Chopra et al (2021) found a substantial rise in the catalepsy bar test that indicated muscle rigidity as of day 7 in the Mn-treated group. In both male and female Mn mice, Freeman et al (2020) noted a decline in rearing behaviour. Males were much more affected than females by the duration of exposure in terms of rearing behaviour.…”
Section: Effect Of Manganese Exposure In Neurobehavioural Alterationmentioning
confidence: 97%
See 2 more Smart Citations
“…et al, 2022). Three studies were conducted in mice (Freeman et al, 2020;Krishna et al, 2014;Wilcox et al, 2022) and five studies in rats (Avila et al, 2010;Muthaiah et al, 2016;Nkpaa, Awogbindin, et al, 2019;Takacs et al, 2012;Zhang et al, 2021).…”
Section: Loe1: Motor and Sensory Functions Endpointsmentioning
confidence: 99%